Knockdown of CIP2A sensitizes ovarian cancer cells to cisplatin: an in vitro study - Zhang, Xiaoli (Int J Clin Exp Med, 2015)
Background: CIP2A is a recently characterized oncoprotein which involves in the progression of several human malignancies. CIP2A is overexpressed in human ovarian cancer and regulates cell proliferation and apoptosis. This study was performed to investigate the role of CIP2A in ovarian cancer (OC) chemoresistance. Methods: Using DDP-resistant SKOV3 cells (SKOV3(DDP)), we first determined the effect of CIP2A silencing by siRNA-mediated knockdown of CIP2A on chemosensitivity in vitro; we then determined the effect of pCDNA3.1-mediated overexpression of CIP2A on chemosensitivity in SKOV3 cells in vitro. To elucidate the molecular mechanisms underlying CIP2A-mediated chemoresistance, the activities of AKT signaling molecules associated with CIP2A were analyzed. Results: Knockdown of endogenous CIP2A in SKOV3(DDP) cells resulted in the reduction in cell growth and increase in the chemosensitivity of SKOV3(DDP) cells to DDP in vitro, which may be caused by CIP2A-induced AKT activity inhibition. Notably, CIP2A overexpression could significantly decrease the sensitivities of SKOV3 cells to cisplatin, which might be ascribed to CIP2A-induced activation of the AKT pathway. Conclusions: Taken together, the results suggest that CIP2A contributes to cisplatin resistance in OC. Thus, CIP2A is a potential therapeutic target for OC.